Effect of Spatial Arrangements on Yield and Competition of Jute (Corchorus Olitorius l.) and Mungbean (Vigna radiata l. Wilczek) in Intercropping (SAARC Journal of Agriculture, 2022)
Low profitability from jute farming, declining jute area and negligible pulse area are the rising concerns of farmers of Indo-Bangla subcontinent. This paper evaluated the extent of yield competition in jutemungbean intercropping with varying spatial geometry under alternate single row (SR) and double row (DR) planting. Two 2-year field experiments were conducted independently for the two systems of plantings involving jute (cv NJ 7010) and mungbean (cv TMB-37) arranged in systematic designs for 3×3×3 spacing and plant density combinations with three replications. Yield competition was assessed using indices. Intercropping was found productive and profitable compared to sole cropping. Land equivalent ratios (LER) and area × time equivalent ratios (ATER) always exceeded unity. Jute equivalent yield (JEY) increased in the range of 4.9-45.3% and 30.7-51.1% over sole jute fibre yield and mean monetary advantage index exceeded 27100 and 31800 ₹ ha-1 for SR and DR planting, respectively. Economic advantage was higher for spacing combinations of 40 cm (row to row) × 6.5-8 cm (jute to jute in a row) × 10-12 cm (mungbean to mungbean in a row) in SR planting and for DR system it was at a band-to-band spacing of 11 cm with plant densities of 40-50 m-2 for jute and 25-30 m-2 for mungbean. Dense and intimate planting of jute reduced mung seed yield due to light stress. DR planting seemed more advantageous. SAARC J. Agric., 19(2): 137-155 (2021)